Real-time leadership find your winning moves when the stakes are high - Noble, David (Boston Harvard Business Review Press, 2023)
The best leaders, in the biggest moments, know how to read the situation, overcome their reflexes, and respond in the best way possible. You can too. The hardest part of leadership is mastering the inevitable high-risk, high-stakes challenges you will face. Whether you're making a split-second decision when your business is hit sideways or finding the best strategy to navigate business-critical long-term circumstances, how can you be at your best in the most crucial moments? It starts with overcoming your leadership reflexes and reactions to find the optimal response to any situation, which you can learn to do. Leadership coaching legends David Noble and Carol Kauffman show you how with their innovative new framework-MOVE-which equips you to slow down high-stakes situations before they speed you up. You'll learn to master the moment, generate options, and quickly evaluate them before acting. As you get better and better using the framework, you'll find you can recognize these moments as they arrive, like a great quarterback who can read defenses at the line of scrimmage, or a great conductor who anticipates what's needed to deliver a great performance. Noble and Kauffman are a dream team who bring decades of experience coaching thousands of leaders, along with a deep base of research, to show why their unique 2-on-1 coaching method works and how it's done. The framework comes to life through the personal stories of real leaders dealing with their own crucible moments. It's a compelling and demystifying look at how leadership coaching delivers results. When the stakes are highest, how can you be at your best? Start by learning this powerful and innovative framework so that you can read and respond-and keep moving forward
Includes bibliographical refeences and index.
Keywords: Leadership